LEGAL PROTECTION OF FAMOUS BRANDS BASED ON LAW NUMBER 20 OF 2016 CONCERNING BRANDS AND GEOGRAPHICAL INDICATIONS - Donny Agus Prakoso; Jeane neltje sally (Journal Equity of Law and Governance, 2024)
Brand protection (including well-known brands) in Indonesia is regulated in Law Number 20 of 2016 concerning Marks and Geographical Indications replacing the previous regulation, namely Law Number 15 of 2001 concerning Marks. Even though there are already regulations in place, brand disputes in Indonesia still often occur, especially similarities in essence. The title adopted by the author in writing this thesis is "Legal Protection of Famous Brands Based on Law Number 20 of 2016 concerning Famous Brands and Geographical Indications." The research method used in this research is a normative legal research method. The purpose of this research is to find out or answer the questions: 1) Does Law Number 20 of 2016 concerning Famous Marks and Geographical Indications provide a guarantee of protection for famous brands in Indonesia? 2) Has Law Number 20 of 2016 concerning Famous Marks and Geographical Indications been truly implemented so that it can guarantee optimal protection of ownership of famous brands in Indonesia? Based on the analysis of the research results, the author concludes that Law Number 20 of 2016 concerning Brands and Geographical Indications has guaranteed protection for well-known brands in Indonesia. This protection is specifically contained in Article 21 paragraph (1) letters b and c, and Article 83 paragraph (2). Then it is clarified in the Explanation of Article 21 paragraph (1) letter b, Explanation of Article 76 paragraph (2), and Explanation of Article 83 paragraph (2). The next conclusion is that Law Number 20 of 2016 concerning Trademarks and Geographical Indications has not been implemented optimally so that it cannot guarantee satisfactory protection of ownership of well-known brands in Indonesia. The Panel of Judges at both the District Court and Supreme Court levels did not implement the mandate of Law Number 20 of 2016